Comparison of Preoperative and Postoperative Serum Calcium and Parathyroid Hormone Levels (Bangladesh Journal of Otorhinolaryngology, 2025)
Introduction: Thyroidectomy is a preferred operation for various thyroid disorders in vasion forms and extent. Postoperative hypocalcaemia and hypoparathyroidism are the common complications. So measuring calcium and PTH level pre and postoperatively is important in planning management of thyroid disease. It can predict the risk of a surgery.Aim of the study: The Aim of the study is to compare serum calcium and parathyroid hormone levels in preoperative and postoperative studies.Methods: A prospective observational study was conducted in the Head and Neck Surgery Division of the Department of Otolaryngology-Head & Neck Surgery, BSMMU, Shahbag, Dhaka from August 2022 to January 2023. 35 patients underwent parathyroidectomy. The data was collected and analyzed using SPSS 26.0 (Statistical Package for the Social Science). The statistical significance was set to p